Selected Webliographies on Indonesian Cultural Heritages - Krismayani Ika (EDP Sciences, 2021)
Indonesia is a country rich in cultural heritage. The diverse cultural heritages demand promotion through various media, such as the web, aimed primarily at the younger generation. This paper aims to present various links and descriptions of web-shaped information sources that participate in promoting the cultural heritage of the Nusantara. The method used is a qualitative descriptive method by searching websites through a search engine using predetermined keywords. The results showed that various websites were found to provide information and promote cultural heritage to the broader community. Dissemination was not only carried out to the Indonesian people but also to the international community. This can be seen from two things, namely the nature of web pages that can be accessed globally and the existence of websites using bilingual, namely Indonesian and English.